Effects of dedollariation policy on the national economy: its advantages and disadvantages - Elemesov Р.Е.; Raimbekova А.А. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
The dependence of the country’s economy on the dollar is considered a key factor in the instability of the foreign exchange market and threatens to lose public confidence in the national currency. In this regard, the government’s policy of dedollarization is one of the key steps in strengthening the role of the national currency in settlements and foreign exchange transactions in the country. The purpose of this article is to identify the main reasons for the de-dollarization policy, analyze the main advantages and disadvantages of the impact of this process on the country’s economy, determine its main consequences for the country, the impact of exchange rate volatility on this process, as well as the level of interest and trust on the part of individuals and corporate investors. Using the latest statistics from the National Bank of Kazakhstan on exchange rates and deposits, there was discussed the impact of the global COVID-19 pandemic on the stability of the national economy and the national currency tenge. The study identified problems that have arisen as a result of the policy of dedollarization. Some key recommendations were made to maximize the effectiveness of government dedollarization policies in the context of floating exchange rates and strong position of dollar in the international foreign exchange market.